Increasing learning innovation through developing teachers’ basic abilities in professional development supervision - Rifma, Rifma; Meizatri, Ranti; Rusdinal, Rudinal; Jasrial, Jasrial (International Journal of Evaluation and Research in Education (IJERE), 2025)
Learning innovation is always related to teacher abilities, emphasizing the design and implementation of innovative teaching and learning. This study aimed to assess the effects of professional development-supervised teacher basic abilities on learning innovation. A total of 409 teachers were engaged as participants. In this case, supervision experience was obtained with a teacher basic ability development approach (commitment and abstraction), as data were analyzed using the partial least square structural equation model (PLS-SEM). The results showed that teacher basic abilities significantly affected the success of professional development supervision and learning innovation. This indicated that the influential levels of the basic abilities on learning innovation and professional development supervision emphasized the t-statistics/p-values of 37.535≥1.96/0.000 and 39.492≥1.96/0.000, respectively. The effects of professional development supervision on learning innovation were also characterized by the t-statistics and p-value of 39.492≥1.96 and 0.000, respectively. Meanwhile, the teacher basic abilities significantly impacted the combined activities of professional development supervision and learning innovation through the t-statistic and p-value of 8.283≥1.96 and 0.000, respectively. These results recommended that principals and supervisors should consider teachers basic abilities as a target in the supervision of professional development, to realize sustainable learning innovations.